(untitled) (American Journal of Islam and Society, 2004)
This book is a delightful read. The somewhat unoriginal title (compilations of conversion accounts under the title Islam Our Choice have been around for several decades, including stories that date back to the mid-twentieth century) belies the original and unique stories told within. However, these words might be rather startling for many non-Muslims, and thus pique their curiosity enough to pick up the book and inquire further. Islam Our Choice, aimed primarily at non-Muslim Americans, tells the stories of fellow Americans who have chosen to follow a different path but who are still Americans. The authors express the hope that “each non- Muslim American reader will probably be able to relate to and identify with the pre-Muslim background of at least one of the authors” (p. 2). The inclusion of family photos and illustrations adds to the book’s visual appeal and shows the contributors as ordinary Americans who are at home with their new identity as Muslims. Although the contributors cover a wide range of geographical locations, levels of education, and career paths, their ethnic and religious backgrounds cover a narrower range. Most of the respondents were former Christians of varying denominations, and most are white; one African-American woman also contributed her story. It is now well known that there are Jewish, Latinos/Latinas, and Native American converts, and, hopefully, their stories will be told in the near future in order to present a fuller picture of how Islam is reaching all sections of American society. The book opens with a brief overview of Islamic faith and practice, Islam in America, and a comparison between the position of women in modern America and in Islam. This sets the scene, as it were, for readers who may be unfamiliar with the Muslim world and with Muslim communities in the West. Written according to the introduction’s general outline, each chapter relates the story of an American woman who has come to Islam. All contributors offer insight into their childhood worlds, whether they were cozy and relatively uneventful, or dogged by poverty and such family troubles as alcoholism. Debra L. Dirks introduces the Mennonite culture from which her family comes, and Khadijah R. Beruni sheds light on the two worlds of her childhood in an extended African-American family: living ...